Предмет: Алгебра,
автор: meksid
2^(8-x)+7^(3-x)=7^(4-x)+2^(3-x)*11 не могу решить
поможет кто?
Ответы
Автор ответа:
0
2^(8-x)+7^(3-x)=7^(4-x)+2^(3-x)*11
2^(8-x)-2^(3-x)*11=-7^(3-x)+7^(4-x)
2^(3-x)*(2^5-11)=7^(3-x)*(7-1)
21*2^(3-x)=6*7^(3-x)
21/6 =7^(3-x) / 2^(3-x)
(7/2) = (7/2)^(3-x)
3-x=1
x=2
2^(8-x)-2^(3-x)*11=-7^(3-x)+7^(4-x)
2^(3-x)*(2^5-11)=7^(3-x)*(7-1)
21*2^(3-x)=6*7^(3-x)
21/6 =7^(3-x) / 2^(3-x)
(7/2) = (7/2)^(3-x)
3-x=1
x=2
Похожие вопросы
Предмет: Физика,
автор: asunafalse
Предмет: Математика,
автор: sssgennn127
Предмет: Қазақ тiлi,
автор: abdazimovasadokat98
Предмет: Физика,
автор: irakaravajeva